2019
DOI: 10.1093/bioinformatics/btz500
|View full text |Cite
|
Sign up to set email alerts
|

Reversible jump MCMC for multi-model inference in Metabolic Flux Analysis

Abstract: Motivation The validity of model based inference, as used in systems biology, depends on the underlying model formulation. Often, a vast number of competing models is available, that are built on different assumptions, all consistent with the existing knowledge about the studied biological phenomenon. As a remedy for this, Bayesian Model Averaging (BMA) facilitates parameter and structural inferences based on multiple models simultaneously. However, in fields where a vast number of alternativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Here, models M i , are structural variants that differ in their bidirectionality setting and, hence, number of flux parameters ( v M i ). Equation (EQ 1) is solved computationally by using a recently developed tailored Markov chain Monte Carlo (MCMC) approach ( 26 ) (see Materials and Methods for details). This results in so-called marginal posterior probability distributions for the net fluxes, as well as the probabilities of reversible reactions being uni- or bidirectional.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, models M i , are structural variants that differ in their bidirectionality setting and, hence, number of flux parameters ( v M i ). Equation (EQ 1) is solved computationally by using a recently developed tailored Markov chain Monte Carlo (MCMC) approach ( 26 ) (see Materials and Methods for details). This results in so-called marginal posterior probability distributions for the net fluxes, as well as the probabilities of reversible reactions being uni- or bidirectional.…”
Section: Resultsmentioning
confidence: 99%
“…Flux inference with Bayesian Model Averaging: Instead of conventional optimization-based single-model flux inference, in this work metabolic fluxes were estimated using a Bayesian multi-model approach. More precisely, net fluxes and reaction bidirectionalities were inferred simultaneously by employing BMA, implemented using a tailored MCMC approach ( 26 ). Herein, 13CFLUX2 was used for likelihood computation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, flux analysis from 13 C-labeling data and parameter estimation from flux and concentration data are based on Monte Carlo sampling methods (Saa and Nielsen, 2016; St. John et al ., 2019; Valderrama-Bahamóndez and Fröhlich, 2019; Theorell and Nöh, 2020) so as generate a representative sample of kinetic models consistent with experimental measurement values and their uncertainties. From such model ensemble, we perform a comprehensive set of analysis regarding parameter distributions, transient dynamical responses, doseresponse properties and gain/loss-of-function phenotypes, which portrays the manner how allosteric regulations contribute to the metabolic response upon oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Random sampling of constraint-based models of metabolism is a powerful approach to characterize the potential behaviors of metabolic networks ( Schellenberger and Palsson, 2009 ; Herrmann et al , 2019 ). The field is actively developed, for example, with recent extensions to model inference ( Theorell and Nöh, 2020 ). Algorithmically, Markov Chain Monte Carlo (MCMC) based coordinate hit-and-run with rounding (CHRR) ( Haraldsdóttir et al , 2017 ) showed superior performance in computational benchmarks ( Herrmann et al , 2019 ) and it is available in a highly efficient and modular implementation ( Jadebeck et al , 2021 ).…”
Section: Introductionmentioning
confidence: 99%